2020
DOI: 10.1038/s41598-020-73604-0
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency oscillations assessed by diffuse speckle contrast analysis for foot angiosome concept

Abstract: An angiosome refers to a 3D tissue volume that is vascularized by a single artery and is a relatively new concept that is useful in vascular surgery; however, the direct relationship between arterial blood flow and micro-perfusion is still controversial. Here, we propose a diffuse speckle contrast analysis (DSCA), which is an emerging tissue perfusion monitoring modality, to investigate the correlations among low frequency oscillations (LFOs) measured from different areas on the feet of healthy subjects. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Though doubts about the real clinical benefit of WDR for both bypass and EVT have been raised in contemporary literature 1-8, 10, 19-21, 32, 37 , using modern microcirculatory diagnostic methods with valuable topographic information 10,19,40,42 . While some authors have found the assessment of anatomical 6,10,16,28 and physiological 16,40,41 angiosomal flow by MRI oximetry 40 , trans-cutaneous laser Doppler 16,28 , or peripheral SPECT-Scan perfusion 10,[41][42][43] useful, others have questioned the utility of topographic reperfusion using white-light tissue spectrophotometry 44 , and low-frequency oscillations analyzed by diffuse speckle contrast analysis 45 . The clinical value of all these studies that support or refute specific postoperative angiosomal microcirculatory changes is indisputable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though doubts about the real clinical benefit of WDR for both bypass and EVT have been raised in contemporary literature 1-8, 10, 19-21, 32, 37 , using modern microcirculatory diagnostic methods with valuable topographic information 10,19,40,42 . While some authors have found the assessment of anatomical 6,10,16,28 and physiological 16,40,41 angiosomal flow by MRI oximetry 40 , trans-cutaneous laser Doppler 16,28 , or peripheral SPECT-Scan perfusion 10,[41][42][43] useful, others have questioned the utility of topographic reperfusion using white-light tissue spectrophotometry 44 , and low-frequency oscillations analyzed by diffuse speckle contrast analysis 45 . The clinical value of all these studies that support or refute specific postoperative angiosomal microcirculatory changes is indisputable.…”
Section: Discussionmentioning
confidence: 99%
“…The graded anatomical scale presented in this study represents an initial observation that needs larger clinical validation. However, our study reveals that not all reported postoperative microcirculatory patterns and measurements 40-45, 47, 51 are performed in equivalent anatomical degrees of CLTI disease 10,43 , and in the corresponding pre-or postreperfusion physiological phases 10,[45][46][47][48][49][50][51] . It also suggests that probably not all previously published studies compare limbs that share similar anatomical and functional collateral indexes, densities of ramifications, and calibers of communicants, and thus do not have equivalent peripheral arterial resistances 8,16,53 that follow distinct territories of angiosomal reperfusion 10,17,49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More details of DSPF and DSCA can be found in [8] and [12] respectively, and in Supplementary Table 1 Both these modalities are increasingly being employed in research studies for biomedical and clinical applications. Since it was developed in 2013, DSCA has been used in studies to assess tissue perfusion for the foot angiosome concept [13] and cerebral blood flow monitoring during middle cerebral artery occlusion (MCAO) in a rodent model [14]. In the former, it was able to measure the low frequency oscillations of blood flow in the foot, showing promising potential to support the diagnosis and monitoring of foot ulcers which is a complication arising from diabetes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Since it was developed in 2013, DSCA has been used in studies to assess tissue perfusion for the foot angiosome concept [13] and cerebral blood flow monitoring during middle cerebral artery occlusion (MCAO) in a rodent model [14]. In the former, it was able to measure the low frequency oscillations of blood flow in the foot, showing promising potential to support the diagnosis and monitoring of foot ulcers which is a complication arising from diabetes [13]. In the latter, it was able to detect the decrease in perfusion in neurological tissue as a result of MCAO, showing potential to observe cerebral hemodynamics associated with transient ischemic stroke [14].…”
Section: Introductionmentioning
confidence: 99%